Associations between postprandial symptoms, hydrogen and methane production, and transit time in irritable bowel syndrome. Issue 2 (11th October 2022) - Algera, Joost P.; Colomier, Esther; Melchior, Chloé; Hreinsson, Jóhann P.; Midenfjord, Irina; Clevers, Egbert; Simrén, Magnus; Törnblom, Hans
Abstract: Background: Abnormal oroanal transit time (OATT) and visceral hypersensitivity are key pathophysiological factors in irritable bowel syndrome (IBS). The lactulose nutrient challenge test (LNCT) has been developed to assess the postprandial symptoms and gut microbial fermentation. We aimed to investigate associations between OATT, rectal sensitivity, and LNCT in IBS patients. Methods: We included 263 IBS patients from two study cohorts, where the link between pathophysiology and symptoms was investigated. During the LNCT, severity of postprandial symptoms was graded, and breath hydrogen/methane concentrations were measured after ingestion of a combined lactulose nutrient drink every 15 min for 4 h. The patients underwent rectal sensitivity (rectal barostat) and OATT (radiopaque markers) investigations. Comorbid conditions (functional dyspepsia, anxiety, depression, and somatization) were assessed with questionnaires. Key Results: After controlling for comorbid conditions, rectal sensitivity was associated with abdominal pain ( p < 0.05), and more rapid OATT was associated with higher severity of abdominal discomfort, rumbling, nausea, and urgency ( p < 0.05 for all) both pre‐ and post‐prandially. Postprandial nausea, urgency, and abdominal pain changed differently over time depending on OATT ( p < 0.05 for all). OATT, but not rectal sensitivity, was associated with hydrogen and methane concentrations ( p = 0.002 for both). Trajectories over time of postprandial symptoms and exhaled hydrogen/methane concentrations were correlated with different correlations depending on OATT. Conclusion and Inferences: This study highlights the importance of oroanal transit and hydrogen and methane production in the pathophysiology of IBS and increases our understanding of pathophysiological factors involved in postprandial symptom generation. Treatments targeting oroanal transit and hydrogen and methane production may improve specific postprandial symptoms. Abstract : Postprandial symptoms, hydrogen and methane production, and oroanal transit time are reciprocally associated in irritable bowel syndrome.